Membangun Jembatan di Atas Jurang: Strategi Inklusi Ekonomi untuk Memperkecil Ketimpangan Sosial di Kawasan Urban - Lilian Martha; Mutiara Tsani (Journal of Community Development and Empowerment, 2026)
Social inequality in urban areas often triggers sharp economic segregation between the upper class and marginalized communities. This community service program aims to implement economic inclusion strategies through a "Building Bridges Over the Chasm" approach to narrow the welfare gap in densely populated urban areas. The implementation method was carried out through three main stages: (1) mapping local assets and economic potential, (2) providing financial and digital literacy training for micro-business actors, and (3) establishing partnership networks between the formal and informal sectors. The results of the activity showed a significant increase in the participants' managerial capacity by 45% and an expansion of market access through digital platforms for local products. This strategy has proven effective in increasing the collective confidence of the community in managing economic resources independently. Through technological integration and cross-sector collaboration, the structural barriers that have long hindered the vertical mobility of urban communities are beginning to erode. The conclusion of this program emphasizes that economic inclusion is not merely about providing capital assistance, but rather about building a supportive and sustainable ecosystem. The recommendation for subsequent programs is the strengthening of local policies that support the protection of small businesses so they can compete amidst the rapid tide of urban gentrification.